Power and Responsibility: Royalty and the Performing Arts in Asante-Ghana. (11th September 2021) - Ampene, Kwasi
Abstract: In all Akan polities, ancestral Black Stools, which belong to the matriclan, are the source of political power and legitimize kingship. Due to the sacred and exclusive nature of stool rituals, Ampene argues that it is the performing arts which define and enhance the power of rulers in the public domain. This ethnographic narrative of the 2014 Grand Worship provides a rare opportunity for the performing arts to project the power and responsibility of the Asantehene when he participates in musical performances and dances.